Batik Motif From The Movement Of Dynamics Harmoic Waves - Sugiyanto; Bariromah; Awliya Amali Tazkiya; Ratna Sinta Dewi; Musyarofah Nurul Maisaroh (Universitas Ahmad Dahlan, 2023)
This batik motif is inspired by the movement of waves in the context of dynamic harmony. Through mathematical and philosophical analysis, wave motion is explored as a symbol of life that constantly changes yet remains harmonious. The methods used include studies on wave displacement, wave partitioning, and the dynamics of waves on a string fixed at one end. Each phase of wave movement is interpreted from the perspective of culture and life values, inviting the viewer to understand the beauty in change and appreciate diversity. Through this motif, the creator wishes to convey that beauty can be found in the dynamic fluctuations of life, inspiring one to face challenges with balance.